Phytochemical, biological, and nutritional properties of the prickly pear, Opuntia dillenii: A review - EL Hassania Loukili; Mohammed Merzouki; Mohamed Taibi; Amine Elbouzidi; Belkheir Hammouti; Krishna Kumar Yadav; Mohammad Khalid; Mohamed Addi; Mohammed Ramdani; Pankaj Kumar; Jeong Ryeol Choi (Saudi Pharmaceutical Journal)
Opuntia (Cactaceae) species are native to arid and semi-arid regions of Mexico and the southern United States and grow in various climatic zones. Opuntia dillenii is a cactus fruit with many beneficial properties, and it is used as a medicinal plant in various countries. This review paper provides updated information on the phytochemical and pharmacological aspects of O. dillenii. The fruit contains valuable compounds such as flavonoids, phenolics, ascorbic acid, betanin, and essential elements, which have been isolated and identified. The fruit also exhibits diverse pharmacological activities, such as antioxidant, anti-inflammatory, anti-tumor, neuroprotective, hepatoprotective, hypotensive, anti-diabetic, antifungal, and anticancer effects. Moreover, molecular docking and ADMET predictions were performed to evaluate the antibacterial potential of the fruit against Escherichia coli protein. This paper suggests that O. dillenii has significant potential as a complementary therapy for various pathological conditions.